Intercepting the malevolent sms in android devices - Lashya Pravallika, A; Bhargavi, B; Harshit, Ch; K. V. D. Kiran, Dr (International Journal of Engineering and Technology, 2018)
Currently, In the mobile operating system Android is trending in the whole world.Though the designers of Android are working much on the security there are few attacks on the messaging framework which are really dangerous. In this paper we also present these attacks. Our focus is on SMS, USSD, and the evolution of their associated security in Android and accordingly the development of related attacks,Also we discuss here the main features and vulnerabilities of Android OS that allow the development and infection by SMS malware.If the SMS is considered as the normal, then it does not take any action and it send to the end user after the delay expires. To deal with this type of issues,we proposed a method where the end user behaviour can be adjusted to prevent the totally malicious SMS.Â Â